Appropriateness of intensive care treatments near the end of life during the COVID-19 pandemic. Issue 2 (June 2020) - Cardona, Magnolia; Anstey, Matthew; Lewis, Ebony T.; Shanmugam, Shantiban; Hillman, Ken; Psirides, Alex
The patient and family perspective on the appropriateness of intensive care unit (ICU) treatments involves preferences, values and social constructs beyond medical criteria. The clinician's perception of inappropriateness is more reliant on clinical judgment. Earlier consultation with families before ICU admission and patient education on the outcomes of life-sustaining therapies may help reconcile these provider–patient disagreements. However, global emergencies like COVID-19 change the usual paradigm of end-of-life care, as it is a new disease with only scarce predictive information about it. Pandemics can also bring about the burdensome predicament of doctors having to make unwanted choices of rationing access to the ICU when demand for otherwise life-saving resources exceeds supply. Evidence-based prognostic checklists may guide treatment triage but the principles of shared decision-making are unchanged. Yet, they need to be altered with respect to COVID-19, defining likely outcomes and likelihood of benefit for the patient, and clarifying their willingness to take on the risks inherent to being in an ICU for 2 weeks for those eligible. For patients who are admitted during the prodrome of COVID-19 disease, or those who deteriorate in the second week, clinicians have some lead time in hospital to have appropriate discussions about ceilings of treatments offered based on severity. Key points: The patient and family perspective on inappropriateness of intensive care at the end of life often differs from the clinician's opinion due to the nonmedical frame of mind. To improve satisfaction with communication on treatment goals, consultation on patient values and inclusion of social constructs in addition to clinical prediction is a good start to reconcile differences between physician and health service users' viewpoints. During pandemics, where health systems may collapse, different admission criteria driven by the need to ration services may be warranted. Educational aims: To explore the extent to which older patients and their families are involved in decisions about appropriateness of intensive care admission or treatments To understand how patients or their families define inappropriate intensive care admission or treatments To reflect on the implications of decision to admit or not to admit to the intensive care unit in the face of acute resource shortages during a pandemic The #COVID19 crisis has raised the importance of and impetus for carrying out early goals-of-care discussions with patients admitted to hospital, especially those whom have been shown to have high risk of death even with ICU admission https://bit.ly/2UNV6cu